AEBP1 is a Novel Oncogene: Mechanisms of Action and Signaling Pathways - Majdalawieh, Amin (2020)
Adipocyte enhancer-binding protein 1 (AEBP1) is a transcriptional repressor involved in the regulation of critical biological processes including adipogenesis, mammary gland development, inflammation, macrophage cholesterol homeostasis, and atherogenesis. Several years ago, we first reported the ability of AEBP1 to exert a positive control over the canonical NF-κB pathway. Indeed, AEBP1 positively regulates NF-κB activity via its direct interaction with IκBα, a key NF-κB inhibitor. AEBP1 overexpression results in uncontrollable activation of NF-κB, which may have severe pathogenic outcomes. Recently, the regulatory relationship between AEBP1 and NF-κB pathway has been of great interest to many researchers primarily due to the implication of NF-κB signaling in critical cellular processes such as inflammation and cancer. Since constitutive activation of NF- κB is widely implicated in carcinogenesis, AEBP1 overexpression is associated with tumor development and progression. Recent studies sought to explore the effects of the overexpression of AEBP1, as a potential oncogene, in different types of cancer. In this review, we analyze the effects of AEBP1 overexpression in a variety of malignancies (e.g., breast cancer, glioblastoma, bladder cancer, gastric cancer, colorectal cancer, ovarian cancer, and skin cancer), with a specific focus on the AEBP1-mediated control over the canonical NF-κB pathway. We also underscore the ability of AEBP1 to regulate crucial cancer-related events like cell proliferation and apoptosis in light of other key pathways (e.g., PI3K-Akt, sonic hedgehog (Shh), p53, parthanatos (PARP-1), and PTEN). Identifying AEBP1 as a potential biomarker for cancer prognosis may lead to a novel therapeutic target for the prevention and/or treatment of various types of cancer.